Isolation and identification of antagonistic Bacillus amyloliquefaciens HSE-12 and its effects on peanut growth and rhizosphere microbial community - Li, Huying; Li, Chaohui; Song, Xin; Li, Jintai; Zhang, Pengcheng; Sun, Fengxia; Geng, Zhigang; Liu, Xunli (Frontiers in Microbiology, 2023)
The HSE-12 strain isolated from peanut rhizosphere soil was identified as Bacillus amyloliquefaciens by observation of phenotypic characteristics, physiological and biochemical tests, 16S rDNA and gyrB gene sequencing. In vitro experiments showed that the strain possessed biocontrol activity against a variety of pathogens including Sclerotium rolfsii. The strain has the ability to produce hydrolytic enzymes, as well as volatile organic compounds with antagonistic and probiotic effects such as ethyleneglycol and 2,3-butanediol. In addition, HSE-12 showed potassium solubilizing (10.54 ±0.19 mg/L), phosphorus solubilisation (168.34±8.06 mg/L) and nitrogen fixation (17.35 ± 2.34 mg/g) abilities, and was able to secrete siderophores ((Ar-A)/Ar×100%: 56%) which promoted plant growth. After inoculating peanut with HSE-12, the available phosphorus content in rhizosphere soil increased by 27%, urease activity increased by 43%, catalase activity increased by 70% and sucrase activity increased by 50% (P<0.05). The dry weight, fresh weight and the height of the first pair of lateral branches of peanuts increased by 24.7%, 41.9% and 36.4% respectively compared with uninoculated peanuts. In addition, compared with the blank control, it increased the diversity and richness of peanut rhizosphere bacteria and changed the community structure of bacteria and fungi. The relative abundance of beneficial microorganisms such as Sphingomonas, Arthrobacter, RB41 and Micromonospora in rhizosphere soil was increased, while the relative abundance of pathogenic microorganisms such as Aspergillus, Neocosmospora and Rhizoctonia was decreased. was found to have 删除[Mr.